Connecting the Dots: Integrating Cultural and Natural Resource Management in the United States - Heilen, Michael; Altschul, Jeffrey H. (Ex Novo: Journal of Archaeology, 2020)
Landholding agencies in the United States are under increasing pressure to integrate cultural and natural resource management approaches at a landscape level and to do so earlier and more comprehensively in planning processes. How to integrate management practices is poorly understood, however. An impediment to integration is that the laws, methods, and tools used in cultural and natural resource management differ significantly. Natural resource management protects or rehabilitates habitats and ecosystems that support endangered species, while cultural resource management focuses on identification and protection of individual sites. Agencies need to shift the focus from managing sites to defining cultural landscape elements and their relationship to natural resource management units and concerns. We suggest that agencies use archaeological predictive modeling, resource classes, and paleoenvironmental and cultural historical information to geospatially define cultural landscapes, predict resource distributions and values, and identify opportunities and protocols for collectively managing cultural and natural resources. As the United States faces increasing deregulation and limited preservation funding, we believe an integrated approach will be critical in preserving and protecting both cultural and natural heritage.